(3eTGQb GdCfhGQ GdfHhjI ef UMGM GdCNHGQ GdeUWahjIs - (3GdQVj GdUGZGfj , GdMSf Hf eMeO Hf GdMSf Hf MjOQ, QVj GdOjf,J (B650 (3g` s ((3HZOGA s)
(3ChdgG (B:s
(3GdMeO ddg eMi GdQee heLQi Gdbde CeG HYO aEfi bO JOQLJ eQGKi GdTQa hJNQLJ ef eSGbi GdTQa s
(3BNQgG (B:s
(3CfS , dHjc YeQI hMLkG Med GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdhQbI GdChdi efgG HNW eZGjQs
(3YdjgG SeGY Ydi CHj GdKfGA eMehO Hf eMeO Hf YeQ GdgQhi HbQGAI LeGYI ef GdCFeIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs